Effect of Al2O3 particle content on microstructure and mechanical properties of 1060Al/Al–Al2O3 composites fabricated by cold spraying and accumulative roll bonding - Zhijuan Zhang; Bing Zhang; Xiaohan Dang; Tianli Zhao; Yingchun Xie; Jun Cai; Kuaishe Wang (Journal of Materials Research and Technology, 2023)
1060Al/Al–Al2O3 laminated particle-reinforced aluminum matrix composites (LPRAMCs) were successfully prepared using a combination of cold spraying (CS) and accumulative roll bonding (ARB) techniques, exhibiting a synergistic improvement in strength and plasticity. The effects of Al2O3 particle content on the microstructure, tensile properties and fracture morphology of LPRAMCs were studied. The results showed that compared with the 1# composites with higher Al2O3 particle content (20.1 vol%), the 2# composites with lower Al2O3 particle content (8.4 vol%) exhibited delayed necking fracture during the ARB process, with greater elongation (El) but lower ultimate tensile strength (UTS). After 5 passes of ARB, the UTS and El of the 1# and 2# composites were 345 MPa, 16.1%, and 293 MPa, 22.2%, respectively. This suggests that the mechanical properties of the Al–Al2O3 deposited layer have a significant impact on the mechanical properties of LPRAMCs. With an increase in ARB passes, the fracture mode of the LPRAMCs shifted from brittle to ductile fracture, displayed by equiaxed and shear dimples. These findings can provide novel insights and theoretical foundations for optimizing the mechanical properties of Al matrix composites.